Proceso editorial de la Gaceta Médica Espirituana. Año 2012. - Manso Fernández, Elizabeth (Gaceta Médica Espirituana, 2012)
El proceso editorial de una revista científica puede compararse con un purgatorio, en él se observa el nivel de preparación científica de los investigadores, se aprecia la cultura de publicación científica de los profesionales; se detectan errores que pudieran tener connotaciones éticas, morales y hasta jurídicas. ABSTRACT The editorial process of a scientific magazine may be compared with a place of purification, in this place the scientific level of preparation of researchers is observed, the culture of scientific publication is valued, and mistakes which could have ethical, moral and legal consequences are corrected.